1991
DOI: 10.1159/000170026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hemodialysis and Hemodiafiltration on Uremic Neuropathy

Abstract: This study was undertaken to compare the effect of 1 year hemodialysis (HD) or hemodiafiltration (HDF) treatment on peripheral neuropathy. Thus 21 of 42 patients on chronic HD (1–1.3 m2 cuprophane dialyzer, Qb 300 ml/min) were switched to HDF (1.3 m2 polysulfone dialyzer, Qb 400 ml/min, substitution volume 9-13 liters, ultrafiltration rate 60-70 ml/min), while the remaining patients were considered as a control group. Treatment time was scheduled both in HD and HDF t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 5 publications
(8 reference statements)
0
19
1
Order By: Relevance
“…While previous studies have emphasised the role of middle molecules as a cause of nerve dysfunction in ESKD [40], [41], there was no significant correlation between PTH, a middle molecule assayed in this study, and pre-RRT measures of nerve excitability. However, while K + was closely related to pre-RRT excitability differences, it cannot explain the during and post-RRT differences between groups.…”
Section: Discussioncontrasting
confidence: 92%
“…While previous studies have emphasised the role of middle molecules as a cause of nerve dysfunction in ESKD [40], [41], there was no significant correlation between PTH, a middle molecule assayed in this study, and pre-RRT measures of nerve excitability. However, while K + was closely related to pre-RRT excitability differences, it cannot explain the during and post-RRT differences between groups.…”
Section: Discussioncontrasting
confidence: 92%
“…Chronic malnutrition, anemia, hypertension, and uremic "toxins," including iPTH, are some of the factors thought to be involved [14,15]. The effect of the mode of dialysis and its efficacy on the evolution of AN has been described in adults and may suggest the role of dialyzable substances [16,17]. As following NTX normal renal function returns, the improvement of AN after transplantation would seem obvious.…”
Section: Discussionmentioning
confidence: 99%
“…The definition of middle molecules has been expanded to incorporate molecules that are not well removed by dialysis for other reasons, including binding moieties and multi‐compartmental behaviour . While the wide range and ambiguity of the middle molecule hypothesis has made it difficult to gain information on specific candidates for targeted therapies in uraemic neuropathy, one study has demonstrated the superiority of large‐pore dialysis membranes in the prevention of peripheral neuropathy . Several of these broad‐definition substrates, such as cytokines and advanced glycation end products, are likely to affect adversely peripheral nerve homeostasis through inflammation and vascular damage .…”
Section: The Pathophysiology Of Peripheral Neuropathy In Ckdmentioning
confidence: 99%